PENGARUH PERTUMBUHAN PENJUALAN, UKURAN PERUSAHAAN, LEVERAGE DAN INTENSITAS MODAL TERHADAP TAX AVOIDANCE - Karista Karista; Murtanto Murtanto (EBID: Ekonomi Bisnis Digital, 2024)
This research aims to identify the influence of sales development, industrial dimensions, leverage, and capital seriousness on Tax Avoidance, either simultaneously or partially, with research objects in the mining manufacturing sector industry listed on the Indonesian Impact Exchange (BEI). The procedure for taking this research illustration uses a purposive sampling method with a total of 66 industries based on the population and 19 selected industries as illustrations. This research design is causal research using quantitative methods and using secondary information. The information analysis method uses the panel information regression method, namely combining cross section and time series information for 4 years from 2019-2022, using the IBM SPSS type 25 application. The results of this research partially prove that sales development, industry dimensions, leverage and seriousness Capital influences Tax Avoidance.